Universal Quantification In The Nominal Domain In Kihehe - Kasper-Cushman, Kelly (My University, 2019)
This study provides a description of the universal quantifiers mbe-agr2-li ‘all’ and kila ‘every’ in Kihehe, a Bantu language spoken in south-central Tanzania. Following a description of general properties of these quantifiers, this study analyzes how the Kihehe data bear on the phenomena of collectivity and distributivity, and situates the Kihehe data with regard to recent crosslinguistic work on the typology of quantifiers (Matthewson 2013).
Keywords: Kihehe; bantu language; Universal quantification; Tanzania